The determinants of secondary jobholding in Germany and the UK - Guido Heineck (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2009)
Secondary jobholding is a persistent phenomenon in both Germany and the UK. Using panel data from the BHPS and the SOEP, reduced form participation equations are estimated for male and female workers separately. Whereas the results vary across gender and countries, there is support for both main theoretical strands, i.e. for the 'hours-constraints' motive and, though less clear, for the 'heterogeneous-jobs' motive.
Keywords: 330; Nebentätigkeit - Determinanten; Mehrfachbeschäftigung; Geschlechterverteilung; Bundesrepublik Deutschland; Großbritannien